Dramaturgi Komunikasi Politik dalam Konstruksi Legitimasi Proses Pencalonan Gibran Rakabuming Raka sebagai Calon Wakil Presiden pada Pemilu 2024: Studi Kualitatif - Fauzie Hikmatussalam Sutrisna (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to analyze the dramaturgy of political communication in constructing the legitimacy of Gibran Rakabuming Raka's nomination as the vice-presidential candidate in Indonesia's 2024 Presidential Election. The research was motivated by the public debate following Constitutional Court Decision No. 90/PUU-XXI/2023, which amended the minimum age requirement for vice-presidential candidates and generated controversies concerning legality, legitimacy, and political ethics. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations of mass media and social media content, and analyses of official documents. The data were analyzed using thematic analysis based on Erving Goffman's dramaturgical perspective and political legitimacy theory. The findings indicate that the construction of legitimacy was shaped through five major dimensions: front stage, back stage, impression management, political symbolism, and audience response. On the front stage, political communication was strategically designed to portray Gibran as a young, adaptive, and approachable leader. Meanwhile, the back stage functioned as the arena for communication planning and issue management. Political symbols, including leadership regeneration, development continuity, and digital transformation, were consistently employed to strengthen the legitimacy of the nomination. Nevertheless, public responses varied according to different interpretations of legal legitimacy, political ethics, and dynastic politics. The study concludes that the legitimacy of Gibran's nomination was constructed not only through procedural legality but also through strategic political communication within the digital public sphere. These findings contribute to the development of political communication studies by extending the application of dramaturgical theory to explain political legitimacy in Indonesia's contemporary democratic context.